Analisis Efektivitas Program Pangan Jajanan Anak Sekolah Aman dalam Perubahan Pengetahuan, Sikap, Perilaku Anak Sekolah di Sulawesi Tenggara - Idrus, Dewi Amni; Agustina, Dian Reni (Eruditio : Indonesia Journal of Food and Drug Safety, 2024)
Snacks are trendy foods with school-age children to fulfil their energy and nutrition needs in the school environment and must be ensured to be safe from biological, chemical, and physical contamination. However, food safety of school snacks program (PJAS) in Indonesia is still a reasonably concerning problem. One of the efforts made by the government to protect school-age children from unsafe PJAS is by increasing the knowledge, behavior, and attitudes of school children in choosing, buying, and consuming food through the Safe PJAS Program. This study aimed to examine the effect of the Safe PJAS program on the knowledge, attitudes, and behavior of school children in Southeast Sulawesi and the effectiveness of the Safe PJAS program in terms of the Knowledge, Attitudes, and Behavior of school children. The research methodology used was the quantitative analysis with Wilcoxon Test and Oneway Anova Test and literature review. The research results showed it was found that the Safe PJAS program carried out in Southeast Sulawesi in 2023 in Wakatobi and Central Buton Regencies had an impact and was influential in increasing the knowledge, attitudes, and behavior of school children in choosing and consuming snack foods. The author's recommendation for the Safe PJAS Program is that the Indonesian FDA can improve coordination and communication with the Ministry of Education and Culture to include food safety material in the independent learning curriculum and increase advocacy to obtain support from the Regional Government in allocating a budget for improving canteen facilities and infrastructure and to replicate the Safe PJAS program.